Morphological Analysis Of The Lower Second Premolar For Age Estimation Of South Indian Adult Population Using Digital Orthopantomogram. - Arun kishore; Dr. Dinesh Kumar (Revista Electronica de Veterinaria, 2023)
Introduction: A panoramic radiograph: a wide view of upper and lower jaw of the denal X-ray. This provides a dual-dimensional from one side of the ear to the other side of the ear. The scan offers various specific details on positioning of the impacted teeth, assessment and treatment planning for various periodontal treatments , orthodontic diagnosis and assessment, jaw damage and various causes of orofacial pain. The aim of the research is to morphologically analyse the lower second premolar among south indian population for age estimation using orthopantomogram. Materials and Methods: In this research 2000 orthopantomogram of both the sexes varying from age 18 to 75 are taken . The OPG images are zoomed using adobe photoshop and is used to measure the lower second premolar area and is pulp area separately with the help of histogram the pixels of lower second premolar and pulp are obtained . Using the obtained information the statistics and results are tabulated Result and Discussion: From the analysed digital orthopantomogram by measuring the pulp/root ration using adobe photoshop. From this method we can say the age difference in the lower second premolar. Conclusion:From the research, it was evident that by using the pulp/root ration of the digital orthopantomogram we can find the estimated age of the tooth.